PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2020 (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2022)
This study discusses the effect of receivables turnover and inventory turnover on profitability in food and beverage companies listed on the Indonesia Stock Exchange in 2014-2020. The data collection technique used in this study is quantitative data obtained from the Indonesia Stock Exchange (IDX) in the financial statements section for data on each ratio. The analytical method used is Panel Data Regression. The results showed that partially for the Accounts Receivable Turnover (X1) variable at tcount < ttable or -0.507570 < -1.99601, the decision was Ho accepted and Ha rejected, meaning that Accounts Receivable Turnover had no significant negative effect on profitability in food and beverage companies listed on the IDX. And the Inventory Turnover variable (X2) obtained the value of tcount < ttable or -0.838780 < -1.99607, then the decision Ho is accepted and Ha is rejected. Based on the F test, the value of fcount > ftable or 5.205996 > 3.13 means that Accounts Receivable Turnover (X1) and Inventory Turnover (X2) have a simil- taneous effect on the profitability of food and beverage companies listed on the IDX. The value of the coefficient of determination (R2) is 0.780656, this shows that 78.06% of the contribution of profitability to food and beverage companies listed on the IDX can be explained by Accounts Receivable Turnover and Inventory Turnover, while the remaining 21.94% can be explained by other variables outside the model such as cash dividends, profit per share. Stocks, interest rates, and rates of return. (Husnah 2016:7).